Food-derived bioactive peptides influence gut function - Moughan, P. J.; Fuller, M. F.; Han, K. S.; Kies, A. K.; Miner-Williams, W. (International Journal of Sport Nutrition and Exercise Metabolism, 2007)
Bioactive peptides either present in foods or released from food proteins during digestion have a wide range of physiological effects, including on gut function. Many of the bioactive peptides characterized to date that influence gut motility, secretion, and absorption are opioid agonists or antagonists. The authors review a body of experimental evidence that demonstrates an effect of peptides from food proteins on endogenous (nondietary) protein flow at the terminal ileum of simple-stomached mammals, including adult humans. At least some dietary peptides (1000-5000 Da) significantly enhance the loss of protein from the small intestine, causing an increased amount of protein to enter the colon. Food-derived peptides appear to either stimulate protein secretion into the gut lumen or inhibit amino acid reabsorption or influence both processes simultaneously. The effect of dietary peptides on small-intestine secretory-protein dynamics is discussed in the context of the major components of gut endogenous protein, sloughed cells, enzymatic secretions, mucin, and bacterial protein.